“This venue is brought to you by…”: the diffusion of sports and entertainment facility name sponsorship in urban Europe - Vuolteenaho, Jani; Wolny, Matthias; Puzey, Guy (Urban geography, 2018)
Drawing on a database of 193 football (soccer) grounds and 115 indoor arenas, as well as press releases and media reports associated with them, this study charts the diffusion of sporting and entertainment facility name sponsorship across metropolises, cities, towns, and smaller settlements in six European contexts. Our results show the emergence of naming rights deals in the 1990s, their peak in the mid-2000s, and the current situation with a steadier growth of name sponsorship. Thus far, the corporate re-branding of venues has remained less prevalent in Italy, Norway, and Scotland than in England and Wales, Finland, and above all Germany. In financing newly built venues, however, the corporatized landmark language in focus has become a practically invariable part of local growth, austerity and (re)branding policies. Despite voices of resistance in all regions studied here, pressure towards the corporate renaming of even hereditary, communally endorsed football stadiums is increasingly being felt by municipal and private-sector venue owners.
Published online: 05 Mar 2018
Gesehen am 25.05.2020